2014
DOI: 10.1002/mus.24294
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound assessment of the diaphragm: Preliminary study of a canine model of X‐linked myotubular myopathy

Abstract: Introduction We tested the feasibility of using neuromuscular ultrasound for non-invasive real time assessment of diaphragmatic structure and function in a canine model of X-Linked Myotubular Myopathy (XLMTM). Methods Ultrasound images in 3 dogs (Wild Type WT, n=1; XLMTM untreated, n=1; XLMTM post AAV8-mediated MTM1 gene replacement, n=1) were analyzed for diaphragm thickness, change in thickness with respiration, muscle echogenicity, and diaphragm excursion amplitude during spontaneous breathing. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Some studies have evaluated diaphragm function using B-mode ultrasonography,26 27 which provides information on the physical form and structure of tissues but only allows subjective evaluation of movement 28. Other studies have used M-mode ultrasonography to observe paralysis of the right diaphragm 29 30.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have evaluated diaphragm function using B-mode ultrasonography,26 27 which provides information on the physical form and structure of tissues but only allows subjective evaluation of movement 28. Other studies have used M-mode ultrasonography to observe paralysis of the right diaphragm 29 30.…”
Section: Resultsmentioning
confidence: 99%
“…M‐mode USG is technically more difficult, particularly in obese patients or when imaging the left hemidiaphragm . Compared with M‐mode USG, B‐mode is more appropriate for measuring precise thickness using the surrounding tissue for reference . We measured diaphragm thickness only at end‐expiration.…”
Section: Discussionmentioning
confidence: 99%
“…In animals, diaphragm ultrasonography has been tested in a canine model of X‐linked myotubular myopathy (Sarwal et al . ) and a recent study showed that this technique could also accurately measure diaphragm movement in wild‐type mice (Zuo et al . ).…”
Section: Introductionmentioning
confidence: 99%